2013
DOI: 10.2147/ijn.s40766
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic nanoparticles of Fe3O4 enhance docetaxel-induced prostate cancer cell death

Abstract: Docetaxel (DTX) is one of the most important anticancer drugs; however, the severity of its adverse effects detracts from its practical use in the clinic. Magnetic nanoparticles of Fe 3 O 4 (MgNPs-Fe 3 O 4 ) can enhance the delivery and efficacy of anticancer drugs. We investigated the effects of MgNPs-Fe 3 O 4 or DTX alone, and in combination with prostate cancer cell growth in vitro, as well as with the mechanism underlying the cytotoxic effects. MgNPs-Fe 3 O 4 caused dose-dependent increases in reactive oxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 34 publications
(35 reference statements)
0
6
0
Order By: Relevance
“… 10 , 11 At present, Fe 3 O 4 is the most common material of nanoparticles with low toxicity, magnetic properties, and metabolizable body. 12 14 The present study is aimed to demonstrate the potential synergistic effects of Fe 3 O 4 -MNP and GA on apoptosis induction in SMMC-7721 cells. The data of MTT assay showed that Fe 3 O 4 -MNP at less than 20 μg/mL concentration had no obvious influence on the multiplication of SMMC-7721 cells but decreased the IC 50 value of GA.…”
Section: Discussionmentioning
confidence: 99%
“… 10 , 11 At present, Fe 3 O 4 is the most common material of nanoparticles with low toxicity, magnetic properties, and metabolizable body. 12 14 The present study is aimed to demonstrate the potential synergistic effects of Fe 3 O 4 -MNP and GA on apoptosis induction in SMMC-7721 cells. The data of MTT assay showed that Fe 3 O 4 -MNP at less than 20 μg/mL concentration had no obvious influence on the multiplication of SMMC-7721 cells but decreased the IC 50 value of GA.…”
Section: Discussionmentioning
confidence: 99%
“…Fe 3 O 4 (100 μg/mL) could decrease 15% cell viability of DU145, PC-3, and LNCaP cells. Fe 3 O 4 (100 μg/mL) could enhance the cytotoxicity of docetaxel (1 nM) in DU145, PC-3, and LNCaP cell lines with 40% cell death [ 94 ]. IONPs coated with luteinizing hormone-releasing hormone receptor (LHRH-R) peptide and urokinase-type plasminogen activator receptor (uPAR) peptide (LHRH-AE105-IONPs) were developed as drug delivery system.…”
Section: In Vitro Applications Of Ionpsmentioning
confidence: 99%
“…The targeted action of IONPs as nanoenhancers is based on the fact these can specifically accumulate in the vascularized part of a solid tumor [91,92], exerting immunogenic and damaging effects at different levels [93][94][95][96]. This was demonstrated when studying iron oxide NPs as independent agents in breast cancer models, e.g., MDA-MB231 [97,98], prostate cancer (e.g., PC3, DU145 [99,100]), liver cancer (e.g., HepG2 [101]), brain tumors (e.g., U87 and GL-261 [102,103]), and others. The accumulation of nanoparticles inside the tumor is possible due to the inherent tumor effect of enhanced permeability and retention (EPR).…”
Section: Antitumor Effects Of Iron Oxide Nanoparticlesmentioning
confidence: 99%